Critical Evaluation of BISAP Score in Assessing the Severity of Acute Pancreatitis: A Prospective Observational Study - Shivarajan, Dhamodhara Kannan; Mehra, Dr Bhupendra; Dubhashi, Dr Siddharth P.; Sherkar, Dr Nitin (International Journal of Innovative Research in Medical Science, 2024)
Background: Early identification of patients at risk of mortality during acute pancreatitis is crucial for improving outcomes. Surgeons have long sought a clinical scoring system that is straightforward, easy to calculate using clinical parameters, and practical to apply. Aim: To evaluate the role of the BISAP scoring system in assessing the severity of acute pancreatitis. Settings and Design: Prospective observational study conducted in a tertiary care centre in central India from Jan 2023 to April 2024. Methods and Material: The study encompassed all patients diagnosed with acute pancreatitis. Within 24 hours of admission, the BISAP score was computed. Additionally, organ failure was assessed using the Marshall Scoring System. Results: Among 190 patients included in the study, there were 174 males and 16 females. The most common aetiology among men was alcoholism, while among women, it was gallstone disease. Of the total 190, 51 patients developed develop organ failure & 18 patients died, with 16 of them having a BISAP score ≥3. The BISAP score demonstrated a sensitivity of 90.64% and a specificity of 84.3% for predicting organ failure. Additionally, it showed a positive predictive value of 94.02% and a negative predictive value of 76.7% in this regard. Conclusion: The BISAP score serves as a valuable tool for risk stratification and prognostic prediction in clinical practice. It is recognized for its simplicity and accuracy in identifying patients early who are at higher risk for mortality and morbidity during hospitalization.